1984
DOI: 10.1128/jb.157.2.380-384.1984
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of a Neurospora crassa extracellular RNase by phosphorus, nitrogen, and carbon derepressions

Abstract: A new extracellular RNase, designated N4, was detected in culture filtrates from Neurospora crassa and its regulation was studied. Limitation of a nutrient obtainable from RNA alone was not sufficient to cause enzyme derepression. The addition of RNA to the medium had no inductive effect, but the addition of exogenous protein caused enzyme production. With protein in the medium, N4 was derepressible for all three elemental nutrients obtainable from RNA: carbon, nitrogen, and phosphorus. Successful carbon derep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
7
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…We have found that RNase N4 is secreted from N. crassa mycelia under three different states of derepression (14). The enzyme probably functions by utilizing external RNA as a source of phosphorus, nitrogen, or carbon, since it is derepressed by limiting any of these three elements.…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…We have found that RNase N4 is secreted from N. crassa mycelia under three different states of derepression (14). The enzyme probably functions by utilizing external RNA as a source of phosphorus, nitrogen, or carbon, since it is derepressed by limiting any of these three elements.…”
mentioning
confidence: 95%
“…By employing the RNase assay described previously (14), we found only one polypeptide with RNase activity in cultures grown for the isolation of extracellular RNase. In each of the three purification procedures, only one peak of activity appeared in the elution profiles from the first chromatography; this activity remained a single peak in subsequent chromatograms.…”
mentioning
confidence: 96%
See 3 more Smart Citations